Desaturase specificity is controlled by the physicochemical properties of a single amino acid residue in the substrate binding tunnel - Buček, Aleš; Vazdar, Mario; Tupec, Michal; Svatoš, Aleš; Pichová, Iva (Computational and structural biotechnology journal, 2020)
Membrane fatty acyl desaturases (mFAD) are ubiquitous enzymes in eukaryotes. They introduce double bonds into fatty acids (FAs), producing structurally diverse unsaturated FAs which serve as membrane lipid components or precursors of signaling molecules. The mechanisms controlling enzymatic specificity and selectivity of desaturation are, however, poorly understood. We found that the physicochemical properties, particularly side chain volume, of a single amino acid (aa) residue in insect mFADs (Lepidoptera: Bombyx mori and Manduca sexta) control the desaturation products. Molecular dynamics simulations of systems comprising wild-type or mutant mFADs with fatty acyl-CoA substrates revealed that the single aa substitution likely directs the outcome of the desaturation reaction by modulating the distance between substrate fatty acyl carbon atoms and active center metal ions. These findings, as well as our methodology combining mFAD mutational screening with molecular dynamics simulations, will facilitate prediction of desaturation products and facilitate engineering of mFADs for biotechnological applications.
Keywords: Enzymatic specificity; Molecular dynamics simulations; Protein engineering; Manduca sexta; Acyl-CoA desaturase; Bombyx mori